Spatialization as a Compositional Tool and Individual Access to Music in the Future: Jonathan Harvey in Conversation with Nicolas Donin - Donin, Nicolas (Circuit)

(untitled) (Les Presses de l'Université de Montréal, 2006)
Beginning by recounting his early contact with Stockhausen's use of moving spatialisation as a compositional parameter, composer Jonathan Harvey discusses how spatial considerations have played a role in his thought (notably under the influence of Bachelard), as well as in his music (especially through the use of the Spatialisateur). He then shares his thoughts on the role of the concert, the domestic context of listening, the possibilities of combining sound and image in home cinema systems, and the ways in which technology can be used as a pedagogical tool for complex music.